An evaluation of climate change effects in estuarine salinity patterns: Application to Ria de Aveiro shallow water system. (5th April 2017) - Vargas, Catarina I.C.; Vaz, Nuno; Dias, João M.
Abstract: It is of global interest, for the definition of effective adaptation strategies, to make an assessment of climate change impacts in coastal environments. In this study, the salinity patterns adjustments and the correspondent Venice System zonations adaptations are evaluated through numerical modelling for Ria de Aveiro, a mesotidal shallow water lagoon located in the Portuguese coast, for the end of the 21st century in a climate change context. A reference (equivalent to present conditions) and three future scenarios are defined and simulated, both for wet and dry conditions. The future scenarios are designed with the following changes to the reference: scenario 1) projected mean sea level (MSL) rise; scenario 2) projected river flow discharges; and scenario 3) projections for both MSL and river flow discharges. The projections imposed are: a MSL rise of 0.42 m; a freshwater flow reduction of ∼22% for the wet season and a reduction of ∼87% for the dry season. Modelling results are analyzed for different tidal ranges. Results indicate: a) a salinity upstream intrusion and a generalized salinity increase for sea level rise scenario, with higher significance in middle-to-upper lagoon zones; b) a maximum salinity increase of ∼12 in scenario 3 and wet conditions for Espinheiro channel, the one with higher freshwater contribution; c) an upstream displacement of the saline fronts occurring in wet conditions for all future scenarios, with stronger expression for scenario 3, of ∼2 km in Espinheiro channel; and d) a landward progression of the saltier physical zones established in the Venice System scheme. The adaptation of the ecosystem to the upstream relocation of physical zones may be blocked by human settlements and other artificial barriers surrounding the estuarine environment. Highlights: Mean sea level (MSL) rise induces a salinity increase all over the lagoon. Projected river flow reduction (RFR) enhances the salinity increase. Future salinity patterns for wet season tend to actual dry season patterns. Saline fronts displace further upstream during spring tide, for MSL rise and RFR. Lagoon borders barriers hamper the equilibrium of relocated ecological zones.